Children's section of the Jaffna Public Library: user satisfaction survey. Issue 1 (1st February 2016) - Chandrasekar, Kalpana; Sivathaasan, Nadarajah
Abstract : Purpose: – This survey research aims to investigate the level of satisfaction among children (up to 14 years) with regard to facilities and services available at the children's section of the Jaffna Public Library (JPL, Sri Lanka). Design/methodology/approach: – A structured questionnaire was distributed among randomly selected members of the children's section, JPL. Data collected via the structured questionnaire were analysed using SPSS 22.0. In addition to the descriptive analysis, independent samples t -test and f -test were conducted to observe the influence of personal variables on different facets of user satisfaction. Findings: – The response rate was 67 per cent. Descriptive analysis showed that the prime purpose of visiting the children's section (JPL) is reading books and other materials. With regard to frequency of visit, 86 per cent of the respondents visit the library three to four times in a week or at least once a week. Results of the f -test indicated that there is no significant difference among different age groups for overall satisfaction of children's section facilities and services. Results of the t -test revealed that female children are more satisfied with the library environment compared to males. Further, the level of satisfaction with shelf arrangement, library environment and children's programmes differed significantly between children studying in the bilingual and the Tamil mediums. Originality/value: – This study reports the empirical findings of the user survey carried out at the children's section of the JPL.